IDENTIFIKASI DAN UJI TOKSISITAS EKSTRAK METANOL DARI DAUN TANAMAN SIRSAK (Annona muricata L) - R. Juliani; Yuharmen '; H. Y. Teruna (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Soursoup (Annona muricata L) was used in herbal medicine. This Annonaceae familymember contains alkaloids, tannins, and several other chemical constituents, includingasetogenin that allegedly to have cytotoxic potential. The n-hexane and methanolmacerating method was applied to isolate the secondary metabolites from the stem barkof this plant. The separation was carried out by vacuum liquid chromatography (VLC),column chromatography, and gel chromatography respectively. Characterization of thefractions was established using UV-Vis and FTIR spectrophotometry. Toxicity assaywas conducted by Brine Shrimp Lethality Test (BSLT) method. The LC 50 of 3 rd to 11 thfractionts of the methanol extract wer 4481.25; 37; 11.46; 0.85; 3.02; 0.23; 10.97; 8.53and 4093 ppm, respectively. The 3 rd and 11 th fractionts were not toxic, whereas otherfractions were toxic and potential to be used as an anticancer.